Determinasi Keputusan Berkunjung Melalui Kepuasan : Analisis Daya Tarik dan Lokasi Wisata Pada Danau Talang Solok - Nofritar Nofritar (Universitas Sains dan Teknologi Komputer, 2021)
The method of collecting data is through surveys and distributing questionnaires to visitors, with a sample of 100 respondents using quantitative techniques. The data analysis technique used is SEM (Structural Equation Modeling) analysis with PLS (Partial Least Square). The results of this study indicate that there is no significant influence of attractiveness on visiting satisfaction and there is a significant influence of location on visiting satisfaction, then there is no significant influence of attractiveness on visiting decisions and there is a significant influence of location on visiting decisions, then there is a significant influence of visiting satisfaction on decisions Visiting and visiting satisfaction cannot mediate the effect of attractiveness on visiting decisions, while visiting satisfaction can mediate the influence of location on visiting decisions.Analysis of Variant (R2) can be seen that the R-square value for the visiting decision variable is 0.788 which can be interpreted that the magnitude of the influence of the attractiveness, location and visiting satisfaction variable on the visiting decision is 78.8% while the remaining 21.2% is explained by the variable others outside of this study. Then the R-square value for the visiting satisfaction variable is 0.634, which means that 63.4% of the visiting satisfaction variable is influenced by attractiveness and location variables, while the remaining 36.6% is influenced by other variables outside of this study.